POLITICAL CLANS OF KYRGYZSTAN: PAST AND PRESENT - BOLPONOVA, Asyl (CENTRAL ASIA AND THE CAUCASUS, 2015)
The author traces the history of the clan system and its evolution as part of the political processes unfolding in Kyrgyzstan. She relies on facts to demonstrate that the clan system of our days is a product of classical unification of tribes into clans.